2018
DOI: 10.1016/j.bpj.2017.11.3446
|View full text |Cite
|
Sign up to set email alerts
|

STAC Proteins Associate to the IQ Domain of CaV1.2 and Inhibit Calcium-Dependent Inactivation

Abstract: The adaptor proteins STAC1, STAC2, and STAC3 represent a newly identified family of regulators of voltage-gated calcium channel (Ca V ) trafficking and function. The skeletal muscle isoform STAC3 is essential for excitation-contraction coupling and its mutation causes severe muscle disease. Recently, two distinct molecular domains in STAC3 were identified, necessary for its functional interaction with Ca V 1.1: the C1 domain, which recruits STAC proteins to the calcium channel complex in skeletal muscle triads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 20 publications
(32 reference statements)
2
30
0
Order By: Relevance
“…Given the similarities between Na V and Ca V channels in regard to CDI (21), similar mechanisms may exist for several isoforms of Ca V s, whereby the position of the EF-hand domain regulates CDI. Interestingly, STAC proteins have recently been found to engage Ca V s (51)(52)(53)(54)(55)(56)(57) and were shown to interact with the EF-hand domain, abolishing CDI (26). This is reminiscent of the effect of FHFs on Na V s, and it was shown that FHFs can abolish CDI in Na V 1.4 (26).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Given the similarities between Na V and Ca V channels in regard to CDI (21), similar mechanisms may exist for several isoforms of Ca V s, whereby the position of the EF-hand domain regulates CDI. Interestingly, STAC proteins have recently been found to engage Ca V s (51)(52)(53)(54)(55)(56)(57) and were shown to interact with the EF-hand domain, abolishing CDI (26). This is reminiscent of the effect of FHFs on Na V s, and it was shown that FHFs can abolish CDI in Na V 1.4 (26).…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, FHFs have been shown to abolish CDI in Na V 1.4 (26), an effect that may be ascribed to its inherent effect on the EF-hand orientation, locking it into a position such that no Ca 2+ -dependent conformational change occurs. Similarly, STAC proteins, which can bind to two different regions in Ca V 1 channels (26,(51)(52)(53)(54)(55)(56), including the EFhand domain (26), could affect the relative orientation between EF-hand and IQ domain. How this conformational change further results in inactivation remains to be shown, but of note is the ability of the EF-hand domain to interact with the III-IV linker, and that this interaction affects channel inactivation (14).…”
Section: Discussionmentioning
confidence: 99%
“…Electron microscopy, structural analysis: Cultures of neurons were prepared as described above with the exception, that neurons were grown on coverglasses coated with a carbon layer as previously described (Campiglio et al, 2018), and fixed with 2% glutaraldehyde (Agar Scientific Ltd., Stansted, UK) in phosphate buffer (PB; 0.1 M, pH 7.4). After washing in PB three times 5 min at RT, neurons were post-fixed and stained with 0.2% osmium tetroxide (Electron Microscopy Sciences, Hatfield, PA) in PB (w/v) for 30 min at RT.…”
Section: Methodsmentioning
confidence: 99%
“…Several years ago, Polster et al (2015) demonstrated that STAC3 facilitates expression and membrane targeting of Ca V 1.1 in tsA201 cells, and later, this function of STAC3 was shown to be due to the interaction of the PKC C1 domain of STAC3 with the C-terminal domain of the DHPR-α 1s (Campiglio et al 2018a;Campiglio and Flucher 2017). This interaction was also shown to play a role in the inhibition of calcium-dependent inactivation of Ca V channels (Campiglio et al 2018a;Niu et al 2018a;Niu et al 2018b); however, it does not appear to be directly relevant to the ECC.…”
Section: Stac3mentioning
confidence: 99%